2019
DOI: 10.1101/850438
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dissecting intratumor heterogeneity of nodal B cell lymphomas on the transcriptional, genetic, and drug response level

Abstract: Tumor heterogeneity encompasses both the malignant cells and their microenvironment. While heterogeneity between individual patients is well-known to affect the efficacy of anti-cancer drugs, most personalized treatment approaches do not account for intratumor heterogeneity. We addressed this issue by studying the heterogeneity of lymph node-derived B cell non-Hodgkin lymphoma (B-NHL) by single cell RNA-sequencing (scRNA-seq) and transcriptome-informed flow cytometry. We identified transcriptionally distinct m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Alignment of sequencing read pairs and variant calling were performed as recently described [66]. Briefly, reads were mapped to human reference genome (hg19) with bwa-mem (version 0.7.8, minimum base quality threshold set to zero [-T 0], remaining settings left to default) [67].…”
Section: Wes and Wgs Data Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Alignment of sequencing read pairs and variant calling were performed as recently described [66]. Briefly, reads were mapped to human reference genome (hg19) with bwa-mem (version 0.7.8, minimum base quality threshold set to zero [-T 0], remaining settings left to default) [67].…”
Section: Wes and Wgs Data Processingmentioning
confidence: 99%
“…SNV and indels in matched tumor normal pairs were identified using the internal DKFZ variant calling workflows based on samtools/bcftools 0.1.19 with additional custom filters (optimized for somatic variant calling by deactivating the pval-threshold in bcftools) and Platypus 0.8.1, respectively, as described previously [66]. Gene annotation of variants was done with Annovar [68].…”
Section: Wes and Wgs Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…For flow cytometry staining, samples were thawed and let rest for 3 h before further processing. LN samples were processed as previously described [44].…”
Section: Processing Of Patient Samplesmentioning
confidence: 99%
“…Recently, the advent of single-cell RNA sequencing (scRNAseq) has enabled detailed surveys of cell subsets in diverse tumor types (Suva `and Tirosh, 2019). For example, scRNA-seq studies identified checkpoint molecule expression on lymphoma-associated T cell subsets (Andor et al, 2019;Aoki et al, 2020) and have uncovered the impact of tumor subclonal heterogeneity on drug response (Roider et al, 2020). While such studies can provide critical insights into clinically relevant cellular diversity, scRNA-seq studies of lymphomas have thus far been of moderate size and are potentially prone to dissociation distortions and patient-specific heterogeneity (Segerstolpe et al, 2016;van den Brink et al, 2017).…”
Section: Introductionmentioning
confidence: 99%